The Effect of Service Quality and Promotion Mix on Purchase Decisions of Gojek Online Transportation Application in Palembang with Customer Satisfaction as a Moderating Variable - Adib Abdul Majid; Diah Natalisa; Muhammad Eko Fitrianto; Iisnawati Iisnawati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The rapid growth of online transportation services has intensified competition, making application service quality and promotional strategies critical factors in shaping consumer purchase decisions. This study analyzes the effects of application service quality and promotion mix on purchase decisions of Gojek users in Palembang City, with customer satisfaction as a moderating variable. A quantitative approach was applied by collecting survey data from 184 active Gojek users and analyzing them using PLS-SEM with SmartPLS 4. The findings reveal that application service quality and promotion mix have positive and significant effects on purchase decisions, with promotion mix as the most dominant factor. Customer satisfaction significantly moderates the relationship between application service quality and purchase decisions, but does not moderate the effect of promotion mix, indicating that satisfaction strengthens performance-based service evaluations while promotional incentives influence purchase decisions independently. These results contribute to digital consumer behavior literature and provide practical implications for improving application performance and optimizing promotional strategies in online transportation services.